Explaining roll call vote request in the European Parliament - Thiem, Janina (2006)
Abstract: This paper investigates determinants of roll call vote (RCV) request in the European Parliament (EP) since studies on voting behaviour based on the RCV sample have proved to be vulnerable to selection bias. At first I argue that party group leaders, who mainly initiate RCVs, cannot be regarded as parliamentary principals of MEPs who use the RCV to discipline their parliamentarians. Owing to the organisational structure of the board of political groups which mainly consists of leaders of (larger) national delegations, it is impossible to clearly differentiate between the party group leader and the leaders of national delegations. As the former do not possess instruments to enforce party group discipline they should not be considered as principals of MEPs but rather as their agents. Party group leaders, I argue, will therefore use RCVs only if they anticipate cohesion to express their group's policy position. Based on this assumption I develop and test a theoretical model of RCV requ